PEMBUATAN GAME HACK AND SLASH 2D “SERENADE TOWER” - Leonardo Leonardo; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
“Serenade Tower” is a hack-and-slash game build for PC platform. Player will play as Hero to slay monster and destroy a tower called Serenade Tower which cause misfortune. “Serenade Tower” use keyboard as the main control to character movement such as moving, attacking and using skill. This game created by Unity game engine with C# as the programming language. Testing has been done by Black Box Testing, Alpha Testing by lecturer and Beta Testing by sharing and doing survey to 30 respondent. The results is the game have neat and nice user interface with balanced gameplay.